PENGARUH LITERASI KEUANGAN TERHADAP PENGAMBILAN KEPUTUSAN KEUANGAN DENGAN PERILAKU KEUANGAN SEBAGAI VARIABEL MEDIASI PADA SISWA SMAN 1 CEMPAGA HULU - Berlianti, Septiani; Christa, Usup Riassy; Widyaningsih, Dhina Sri; Haga, Ronni (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
This study examines the effect of financial literacy on financial decision making with financial behavior as a mediating variable. The main problem addressed in this research is the inconsistency of individual financial decisions despite having access to various financial products and services. The objective of this study is to analyze the direct effect of financial literacy on financial decision making, the effect of financial literacy on financial behavior, the effect of financial behavior on financial decision making, and the mediating role of financial behavior in the relationship between financial literacy and financial decision making. This research uses a quantitative approach with data collected through questionnaires distributed to respondents. Data analysis was conducted using Structural Equation Modeling with the Partial Least Squares approach, supported by SmartPLS software. The results show that financial literacy has a positive and significant effect on financial decision making. Financial literacy also has a positive and significant effect on financial behavior. Furthermore, financial behavior positively and significantly influences financial decision making. The indirect effect test indicates that financial behavior partially mediates the relationship between financial literacy and financial decision making. These findings suggest that improving financial decision quality requires not only adequate financial knowledge but also the development of positive financial behavior. The study concludes that financial behavior plays an important role in translating financial literacy into better financial decision making.